Melatonin: a modulator in metabolic rewiring in T-cell malignancies - Rai, Seema; Roy, Gunja; Hajam, Younis Ahmad (Frontiers in Oncology, 2024)
and cellular glycolytic activity. Further, melatonin plays a modulatory role in the expression of essential transporters (Glut1, Glut2) responsible for nutrient uptake and metabolic rewiring, such as glucose and amino acid transporters in T-cells. This modulation significantly impacts the metabolic profile of T-cells, consequently affecting their differentiation. Furthermore, melatonin has been found to regulate the expression of critical signaling molecules involved in T-cell activations, such as CD38, and CD69. These molecules are integral to T-cell adhesion, signaling, and activation. This review aims to provide insights into the mechanism of melatonin's anticancer properties concerning metabolic rewiring during T-cell malignancy. The present review encompasses the involvement of oncogenic factors, the tumor microenvironment and metabolic alteration, hallmarks, metabolic reprogramming, and the anti-oncogenic /oncostatic impact of melatonin on various cancer cells.